A Preliminary Report on Prevalence of Antibody Response to GBV-C, E2 Protein in Iranian Blood Donors and Multitrans-fused Patients - H Rezvan; M Sharafi; H Shams; M Mahmoodian Shooshtari (Tehran University of Medical Sciences, 2007)
Background: To analyze serologic markers of Hepatitis G virus (GBV-c) infection in Iranian blood donors and two major groups of multitransfused patients, hemophiliacs and thalassemics. Methods :Nine hundred and five serum samples collected from the volunteer blood donors and two patient groups under the study were tested for the presence of antibodies to the GBV-C antigen (anti E2 ) by an ELISA assay .Those found positive for anti- E2 were also tested for possible exposure to HCV by detecting anti- HCV in their sera. Levels of ALT were also tested to evaluate impact on liver function. Results: Approximately 8.6% of the volunteer blood donors were found positive for anti-E2 .The prevalence rate in hemophiliacs was 41.4 % and in thalassemia patients was 33.4% , which was significantly (P< 0.05) higher than donors. However, the prevalence rate among the two high risk groups was not statistically significant. Conclusion: A large number of the healthy blood donors in Iran have been exposed to the GBV-C. The significantly higher levels seen in the multitransfused patients can be regarded as an important route of transmission. It seems that no evidence of liver damage in individuals exposed confirming that GBV-C is not a hepatitis virus.